Neurologists' Assessment of Mental Comorbidity in Patients With Vertigo and Dizziness in Routine Clinical Care—Comparison With a Structured Clinical Interview - Limburg, Karina; Dinkel, Andreas; Schmid-Mühlbauer, Gabriele; Sattel, Heribert; Radziej, Katharina; Becker-Bense, Sandra; Henningsen, Peter; Dieterich, Marianne; Lahmann, Claas (Frontiers in Neurology, 2018)
Background: Mental health comorbidities are frequent in patients with vertigo and dizziness. The current study was conducted in a specialized interdisciplinary university center for vertigo and dizziness. Clinical routines consist of a structured work-up in which neuro-otological and neurological tests are performed to first detect possible organic vestibular deficits. In addition, psychiatric disorders and comorbidities are considered. The study aimed to evaluate neurologists’ awareness of psychiatric next to somatic disorders within patients’ first examination in terms of diagnostic congruence between neurologists' diagnoses and structured clinical assessment of mental disorders. Methods: The study involved 392 patients. Diagnostic evaluation included a) structured history-taking (including psychosocial anamnesis), neurological, and neuro-otological diagnostics conducted by neurologists and b) a structured clinical interview for mental disorders (SCID-I) conducted by psychologists and final-year medical or psychology students. Cohen’s Kappa was calculated to determine agreement rates regarding depression and anxiety disorders; additionally, sensitivity and specificity were evaluated. Results: Neurologists' assessments led to at least one psychiatric diagnosis among the main diagnoses in 40 (10.2 %) patients, whereas the structured clinical interview led to at least one DSM-IV psychiatric diagnosis in 174 (44.4 %) of the patients. Agreement was low (κ < 0.2); sensitivity was low (15 %) but specificity was high (98 %). Conclusions: Agreement between the diagnosis of neurologists and structured clinical interviews for psychiatric disorders is low. Since psychiatric disorders are frequent in vertigo and dizziness and tend to take a chronic course, improving early recognition and implementing appropriate care concepts is vital.